Task design for online learning: the case of middle school mathematics and science teachers - Daher, Wajeeh; Shayeb, Shaheen; Jaber, Reema; Dawood, Iman; Abo Mokh, Amnah; Saqer, Khitam; Bsharat, Maysa; Rabbaa, Mohammad (Frontiers in Education, 2023)
Introduction Teachers' task design in the context of online learning has been little researched by educational researchers. The current research examines the task design of science or mathematics teachers in the context of distance education based on the didactical situation theory and, in particular, situation types. Methods Fourteen teachers participated in the current study. They were interviewed regarding the situation types that they used to design online tasks. We used both deductive and inductive methods to analyze the transcribed interviews. Results The research findings showed that the teachers utilized different categories of the situation types. Moreover, the teachers utilized three types of reference as follows: the institution, the individual, and the tool. The participating mathematics and science teachers attempted to integrate argumentation into their designed tasks. Furthermore, the situation of communication was designed by the participating teachers to enable the interaction between and inside different agents of online education (students, teachers, and parents) while utilizing different communicational channels (mobile social networks, Zoom rooms, Zoom sessions, student's homes, and Google Classroom). The teachers designed situations of action to address the various aspects of learning, namely, the cognitive, social, affective, and psychological aspects. Discussion We argue that the design of online tasks could utilize the didactical situation of action, where the online students are requested to reflect critically on the online tasks. We recommend that teachers request reflection and feedback from their students regarding the tasks that they design for online learning.